Personalising Outcomes after Child Cardiac Arrest (POCCA): design and recruitment challenges of a multicentre, observational study - Fink, Ericka L (BMJ Open, 2020)
INTRODUCTION: Blood and imaging biomarkers show promise in prognosticating outcomes after paediatric cardiac arrest in pilot studies. We describe the methods and early recruitment challenges and solutions for an ongoing multicentre (n=14) observational trial, Personalising Outcomes following Child Cardiac Arrest to validate clinical, blood and imaging biomarkers individually and together in a clinically relevant panel. METHODS AND ANALYSIS: Children (n=164) between 48 hours and 17 years of age who receive chest compressions irrespective of provider, duration, or event location and are admitted to an intensive care unit are eligible. Blood samples will be taken on days 1–3 for the measurement of brain-focused biomarkers analysed to predict the outcome. Clinically indicated and timed brain MRI and spectroscopy biomarkers will be analysed to predict the outcome. The primary outcome for the trial is survival with favourable (Vineland Adaptive Behavioural Scale score >70) outcome at 1 year. Secondary outcomes include mortality and pre-event and postdischarge measures of emotional, cognitive, physical and family functioning and health-related quality of life. Early enrollment targets were not met due to prolonged regulatory and subcontract processes. Multiple, simultaneous interventions including modification to inclusion criteria, additional sites and site visits were implemented with successful improvement in recruitment. Study procedures including outcomes and biomarker analysis are ongoing. ETHICS AND DISSEMINATION: Twelve of 14 sites will use the centralised Institutional Review Board (IRB) at the University of Pittsburgh (PRO14030712). Two sites will use individual IRBs: Children’s Healthcare of Atlanta Institutional Review Board and Children’s Hospital of Wisconsin IRB. Parents and/or guardians are consented and children assented (when possible) by the site Primary investigator (PI) or research coordinator for enrollment. Study findings will be disseminated through scientific conferences, peer-reviewed journal publications, public study website materials and invited lectures. TRIAL REGISTRATION NUMBER: NCT02769026.